Direito à saúde: necessidade de proteção e meios de efetivação - Brandão, Magno Cardoso (2009)
The Federal Constitution of 1988 lists several principles for the protection of citizens, to assure compliance with citizenship and human dignity. Therefore, the State has the duty to observe these principles in order that we can give equal access to all individuals who sought public health services, as recommended by the art. 6 c / c 196, of the Constitution, which deals with the state's obligation to provide health services in full and free for those in need. There is also a vast constitutional legislation regulating the protection, promotion and restoration of health. So, given that health is a fundamental right of all social and obligation of the Government, should be provided with efficiency, by the State. Therefore, the role of bodies responsible for provision of health services, mainly to the National Health System, to promote proper enforcement. Since often these bodies do not comply with its constitutional duty. This work aimed to precisely check the proper realization of the right to health for all guarantees and principles existing in Brazilian law are respected. The effect was the need to examine the state's responsibility and the means of realization of such a service, showing the importance of providing health service, the existing problem as well as the duty of the state and its possible liability, and also analyzing the means of ensuring the right to health, applicable laws and the attitudes of the Brazilian Justice on the matter. He tried to find solutions for the improvement and proper realization of the health service.